2007
DOI: 10.1124/dmd.107.018556
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein Restricts the Penetration of Oseltamivir Across the Blood-Brain Barrier

Abstract: ABSTRACT:Oseltamivir is an ethyl ester prodrug of [3R,4R,5S]-4-acetamido-5-amino-3-(1-ethylpropoxy)-1-cyclohexene-1-carboxylate phosphate (Ro 64-0802), the anti-influenza drug. Abnormal behavior has been suspected to be associated with oseltamivir medication in Japan. The purpose of the present study is to examine the involvement of transporters in the brain distribution of oseltamivir and its active form Ro 64-0802 across the blood-brain barrier (BBB). The brain-to-plasma concentration ratio (K p,brain ) of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 34 publications
(38 reference statements)
6
94
1
Order By: Relevance
“…Various studies have demonstrated that the penetration of a vast variety of drugs across the blood-brain barrier (BBB) is determined by Pgp (Schinkel et al, 1997;Chen et al, 2003;Ose et al, 2008). Similar to Pgp, the expression of Bcrp on the luminal membrane of brain endothelial cells has been demonstrated (Daood et al, 2008;Roberts et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have demonstrated that the penetration of a vast variety of drugs across the blood-brain barrier (BBB) is determined by Pgp (Schinkel et al, 1997;Chen et al, 2003;Ose et al, 2008). Similar to Pgp, the expression of Bcrp on the luminal membrane of brain endothelial cells has been demonstrated (Daood et al, 2008;Roberts et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, however, there have been postmarketing reports (mostly from Japan) of neuropsychiatric side effects in younger patients taking oseltamivir, in some cases resulting in fatal outcomes (http://www.gene.com/gene/products/information/tamiflu/pdf/pi.pdf). This finding has led to a number of studies evaluating the mechanism by which oseltamivir and oseltamivir carboxylate are transported across capillary endothelial cells forming the blood-brain barrier (Morimoto et al, 2008;Ose et al, 2008Ose et al, , 2009. It was demonstrated that oseltamivir and its active metabolite were actively effluxed by luminally expressed P-glycoprotein (Pgp) and multidrug resistance-associated protein 4, respectively, thereby limiting their penetration in brain.…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments with rodents demonstrate that orally (30 -300 mg/ kg) or intravenously (8 µmol / h per kg) administered oseltamivir accumulates in the brain via the blood-brain barrier, the brain-to-plasma concentration ratio ranging from 0.1 -0.7 (roughly equal to 0.1 -5 µM in the brain) (13,14). Safety examinations of Tamiflu TM (oseltamivir), conducted by Roche, show that in 7 -14-day-old rats, the brain concentration reaches more than 500 times greater than that in adult animals (see basic product information of Tamiflu TM ), suggesting a higher risk of a side-effect in younger brains.…”
mentioning
confidence: 99%